Peran Agroforestri Dalam Mendukung Pengelolaan Sumberdaya Alam Berkelanjutan - Muhammad Yul Fikry; Muhammad Sarjan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Agroforestry, a farming system that integrates various types of perennial and seasonal crops, as well as livestock elements, has emerged as an alternative in many regions to enhance farmers' income, protect the environment, and address local economic challenges. The role of agroforestry in supporting sustainable natural resource management is crucial. This system helps maintain soil fertility, reduce erosion, regulate hydrological patterns, sequester carbon, and enhance biodiversity. Moreover, agroforestry also contributes to improving farmers' food security through diverse and sustainable yields, as well as strengthening the economic and social sustainability of communities. Despite some challenges in increasing agroforestry productivity, its implementation is expected to address issues related to forest land conversion, enhance food security, and make a significant contribution to maintaining environmental balance and overall community welfare.